Association between radionuclides (210Po and 210Pb) and antioxidant enzymes in oak (Quercus coccifera) and mastic tree (Pistacia lentiscus) - Uğur Görgün, A.; Aslan, E.; Kül, M.; İlhan, S.; Dimlioğlu, G.; Bor, M.; Özdemir, F. (Journal of environmental radioactivity, 2017)
The activity levels of naturally occurring radionuclides Polonium-210 and lead-210 in different subjects including plant species have direct or indirect impact on human beings. High levels of ionising radiation cause oxidative stress and the interaction between antioxidative defense and radionuclides is not well established in plant systems. In this study, we aimed to understand the impact of oxidative stress caused by 210Po and 210Pb in two Mediterranean plants; Quercus coccifera and Pistacia lentiscus. We analysed the constitutive and seasonal levels of 210Po, 210Pb, lipid peroxidation levels, superoxide dismutase (SOD) and ascorbate peroxidase (APX) activities in the field-collected samples. The highest activity concentrations of 210Po and 210Pb were detected in both plants in summer and Q. coccifera had higher levels than that of P. lentiscus. SOD and APX activity trends were different between oak and mastic; as compared to P. lentiscus, Q. coccifera efficiently used the two major components of antioxidative defense. Lipid peroxidation levels were low in both plants in all seasons except that of spring which were in good agreement with high antioxidant enzyme activities. In conclusion, we found that high 210Po and 210Pb activity concentrations in oak and mastic did not interfere with their growth and life cycles. The ability of both plants for survival and adaptation to Mediterranean environmental constraints provided an additional advantage for coping radionuclide induced oxidative stress as well. •High levels of ionising radiation cause oxidative stress.•Mediterranean plants oak and mastic tree had high 210Po and 210Pb levels.•210Po and 210Pb levels didn't interfere with their growth and life cycles.•High SOD and APX activities were effective in radionuclide induced oxidative stress.